Cereals, pulses, legumes and vegetable proteins (Food and Agriculture Organization of the United Nations,World Health Organization, 2008)
The designations employed and the presentation of material in this information product do not imply the expression of any opinion whatsoever on the part of the Food and Agriculture Organization of the united nations(FAO) concerning the legal or development status of any country, territory, city or area or of its authorities, or concerning the delimitation of its frontiers or boundaries.